2012
DOI: 10.1016/j.drugalcdep.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine increases the motivation to obtain non-drug reinforcers in rats

Abstract: BACKGROUND Caffeine is widely considered to be a reinforcer in humans, but this effect is difficult to measure in non-human animals. We hypothesized that caffeine may have dual reinforcing effects comparable to nicotine - limited primary reinforcing effects, but potent reinforcement enhancing effects. The present studies tested this hypothesis by investigating the effect of caffeine on responding for non-drug rewards. METHODS In two experiments, rats were shaped to respond on a progressive ratio (PR) schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 59 publications
(73 reference statements)
3
12
1
Order By: Relevance
“…Studies should continue examining potential mechanisms, such as relating changes in brain activation due to acute nicotine to its reinforcement enhancing effects (e.g., Klinkenberg et al 2013; Paterson, 2009; Wise, 1998). Finally, reinforcement enhancing effects of other drugs of abuse warrant study as they may very well be similar to those observed here with nicotine via smoking (e.g., Lloyd et al, 2012; Sheppard et al, 2012). …”
Section: Discussionsupporting
confidence: 53%
“…Studies should continue examining potential mechanisms, such as relating changes in brain activation due to acute nicotine to its reinforcement enhancing effects (e.g., Klinkenberg et al 2013; Paterson, 2009; Wise, 1998). Finally, reinforcement enhancing effects of other drugs of abuse warrant study as they may very well be similar to those observed here with nicotine via smoking (e.g., Lloyd et al, 2012; Sheppard et al, 2012). …”
Section: Discussionsupporting
confidence: 53%
“…This hypothesis is supported by findings showing that caffeine produced nicotine-like discriminative stimulus effects in a substitution task [63]. The interaction between caffeine, nicotine and nicotine-associated cues on relapse to nicotine use is important to our understanding of factors that maintain nicotine and tobacco use in humans; however, further exploration is needed the given conditioned reinforcement-enhancement effects of both drugs and the high rate of NIC and CAF co-use [62,64]. …”
Section: Discussionmentioning
confidence: 86%
“…Cousins, Stamat, & deWit, 2001). Finally, although we confirmed overnight smoking abstinence and ad lib exposure prior to sessions, we did not biochemically assess other potential recent drug use, which could possibly affect responding for rewards (e.g., Sheppard et al 2012). …”
Section: Discussionmentioning
confidence: 87%